PENGARUH KOMPETENSI DALAM MENINGKATKAN KINERJA SUMBER DAYA MANUSIA: SEBUAH STUDY EMPIRIS - Reijeng Tabara (SOSCIED, 2020)
The aim of this research is to learn about the impact of competence on the performance of human resources. The type of research used is Explanatory Research aimed at testing a relationship hypothesis among variables. This study used questionnaires as tools to obtain data, spreading them with Non-probability Sampling with a simple random sampling technique against 41 teachers. A structural equatin model (SEM) with SmartPLS 2.0 M3 is the analytical technique used. The finding showed that there was a positive and important effect on human resource efficiency across competencies, with a TStatistics value of 7,757 > Ttable 1,682. The effect of skill in improving the performance of human resource at teacher in district X, Sorong Regency of West Papua has various limitations, among others, with the limitations of existing teachers causing representation on a district scale cannot generalize the overall teacher in the District Government of Sorong, West Papua